Corporate social responsibility and board gender diversity: A meta-analysis - Wu, Qichun (Emerald Group Holdings Ltd., 2022)
Purpose: The importance of board composition, especially female directors’ presence on boards, is thought to influence corporate responsibility performance, has attracted significant scholarly interest. This study aims to examine how board gender diversity (BGD) affects corporate social responsibility (CSR) performance and the moderating factors that influence the relationship. There is a lack of research on the moderating indicators (variable measurement, geographic location, data sets and gender parity score) that impact the BGD and CSR relationship. Design/methodology/approach: This study uses content analysis and meta-analysis to combine the findings of 44 selected papers published from 2010 to 2019, comprehensively reviewing the academic literature on gender diversity in the board composition. Independent and dependent variables are classified based on the variable measurement; this study examines the moderator indicators, such as geographical location, research data sets and gender parity score to investigate the BGD and CSR relationship. Findings: The findings indicated a significant positive relationship between BGD and CSR performance. The meta-method results showed that the measurements of BGD and CSR limited to impact on the relationship. But a significant moderating effect of the geographical location on the BGD-CSR relationship, the BGD-CSR relationship would be stronger in the firms located in North America than firms located in Asia and other areas. Empirical results also showed a significant moderating effect of gender parity score. There would be stronger BGD-CSR relations in the firms located in the countries with higher gender parity score than the firms located in the countries with low gender parity score. This means the female status is an essential indicator of moderating the BGD-CSR relationship. Research limitations/implications: The main shortcoming is a lack of sufficient articles on the BGD-CSR relationship. In a future study, researchers may use other databases, such as Google scholar or Ebscohost, to increase the number of relevant articles. These studies would offer new insight into the meta-analysis of the relationship between the BGD and CSR. Finally, the authors identify the potential trend in future research, future research on BGD will need for standardized metrics. The Geographic location is an important indicator that will influence the female director role in CSR. A systematic measure and data of gender research are more important for study in this field. Practical implications: Meta-analysis is conducted on the independent and dependent variables to examine the causality between BGD and CSR performance, which could better explore diversity among different countries’ boards and, more generally, to investigate the degree to which diversity may influence CSR. Firms may try to balance the BGD to improve future development prospects. Specifically, the results of this study have important implications for corporate governance and policymakers. Social implications: First, this systematic study uses meta-analysis to combine the findings of previous research on the BGD-CSR. The current research attempts to incorporate mixed empirical results based on the different variable measurements. Second, this study develop and test a contingency model of female on boards and CSR that considers uses the geographic location factors that may enhance or diminish the influence of female on boards on CSR. Specifically, the authors examine whether and under what conditions, boards with more female directors differ for inter-country heterogeneity to which they engage in monitoring roles and are involved with strategy management. Originality/value: First, this study could be the first systematic study that uses the meta-analysis to combine previous research findings on the BGD-CSR. Second, the current research attempts to incorporate mixed empirical results based on the different variable measurements. Third, this study uses the “gender parity score” to account for inter-country heterogeneity in the BGD-CSR relationship. This study also identifies the potential trend in future research. © 2021, Emerald Publishing Limited.